Effect of College Students’ Smartphone Addiction on Academic Achievement: The Mediating Role of Academic Anxiety and Moderating Role of Sense of Academic Control - Zhang J; Zeng Y (Psychology Research and Behavior Management, 2024)
Jiahui Zhang,* Youlai Zeng* Department of Education, Liaoning Normal University, Liaoning, Dalian, 116029, People’s Republic of China*These authors contributed equally to this workCorrespondence: Youlai Zeng, Email 382765058@qq.comBackground: College students are the backbone of future national construction and shoulder the hope of the future development of the country and the nation. Smartphone addiction among college students will not only affect their own mental health and learning attitude, but it will also significantly affect their future academic achievement, academic emotion and academic engagement. However, the relationship between academic anxiety and academic control and academic achievement, as well as their internal mechanisms and boundary conditions, has received little attention. The purpose of this study is to examine whether and how smartphone addiction influences academic achievement.Purpose: This study aims to explore the mechanistic role of academic anxiety and academic control in the influence of smartphone addiction on academic achievement in college students, and hopes that the results can guide education and teaching.Methods: A sample of N=2097 participants, this study evaluated the relationship between smartphone addiction, academic control, academic anxiety and academic achievement among college students, and the participants filled in the college students’ smartphone addiction scale, academic control questionnaire, academic anxiety questionnaire and grade points.Results: (1) There is a significant negative correlation between smartphone addiction and academic achievement; (2) academic anxiety serves as a complete mediator in the relationship between smartphone addiction and academic achievement; (3) the interaction between smartphone addiction and academic control moderates academic anxiety, with higher levels of academic control associated with a weaker impact of smartphone addiction on academic anxiety; (4) academic control also moderates the mediating role of academic anxiety between smartphone addiction and academic achievement, demonstrating a moderated mediating effect.Conclusion: Smartphone addiction had negative direct effect on academic achievement, as well as completely mediating effect through academic anxiety. Academic control moderated the relationship between of smartphone addiction and academic anxiety. This study enriches the research on the relationship between smartphone addiction and academic achievement in theory, and has important guiding significance for education and teaching in practice.Keywords: smartphone addiction, academic anxiety, sense of academic control, academic achievement